Intra-Host Diversity and Emergence of Unique GBV-C Viral Lineages in HIV Infected Subjects in Central China - Wu, Haoming; Padhi, Abinash; Xu, Junqiang; Gong, Xiaoyan; Tien, Po (PLOS ONE, 2012)
GB virus C (GBV-C), which is highly prevalent among HIV/AIDS, seemed to slow the HIV disease progression. The HIV/GBV-C co-infected individuals may represent an interesting model for the investigation of the role played by HIV infection and/or the immune system in driving the evolution of the GBV-C viral populations. The present study investigated the prevalence and population dynamics of GB virus C in HIV infected individuals representing 13 geographic regions of Hubei Province of China. Approximately 37% of HIV-1 infected individuals were infected with GBV-C and genotype 3 is appeared to be predominant. Utilizing the 196 complete E2 nucleotide sequence data from 10 HIV/GBV-C infected individuals and employing coalescence based phylogenetic approaches; the present study has investigated the intra-host dynamics of GBV-C. The results revealed patient-specific unique GBV-C viral lineages and each viral lineage showed the evidence of rapid population expansion in respective HIV-1 infected patients, thus suggesting HIV-1 was unlikely to have been inhibiting effect on the GBV-C viral replication. GBV-C in all patients has experienced intense purifying selection, suggesting the GBV-C viral invasion and subsequent expansion within the HIV-1 infected hosts without any modification of the functional epitopes at their membrane protein. The finding of within host GBV-C recombinant sequences indicated recombination was one of the significant forces in the evolution and divergence of GBV-C.